P171 Development of an ex-vivo patient-derived explant model for predicting drug responses in endometrial cancer. (1st November 2019) - Collins, A; Miles, G; MacFarlane, M; Pritchard, C; Moss, E
Abstract : Introduction/Background: Adjuvant chemotherapy confers a modest advantage in progression free and overall survival in endometrial cancer (EC). Response rates to primary chemotherapy regimens are reported as low as 17–36% 1 . Pre-clinical models that better predict patient outcomes to standard of care and novel anti-cancer treatments are urgently required. Patient derived explants (PDEs) retain histological 3D architecture of the primary tumour, preserve intra-tumour heterogeneity and maintain patient specific stromal cells including tumour associated fibroblasts and immune cells. This project aims to establish optimal culture conditions for EC-PDEs and to evaluate patient-specific responses to SOC chemotherapies. Methodology: Fresh tumour was obtained post-hysterectomy from patients with EC. Tumour was dissected into 1-3 mm 3 explants and placed on PVDF filter inserts in culture media and cultured at the air-liquid interface. Following overnight recovery, explants were moved to fresh media and cultured for 24 hours, optimal media conditions were established and explants were cultured with carboplatin, paclitaxel & pembrolizumab. Multiplexed fluorescent immunohistochemistry for Ki67 (proliferation marker), cleaved PARP (apoptosis marker) and CAM 5.2 (tumour mask) was performed followed by quantitative analysis to evaluate cellular proliferation and apoptosis in tumour and stroma. Results: Tissue architecture and histology were maintained in PDE culture. Mean tumour cleaved-PARP% at T0 control was 1.4%, increasing to 14.8% following 48 hours (T48) culture in DMEM-F12 media. Autologous serum (AS) supplementation at low concentrations (1%) reduced tumour apoptosis at T48 to 6.7%. Higher concentrations of fetal calf serum/AS resulted in a dose-dependent increase in apoptosis while addition of oestrogen did not confer additional benefit. Explants treated with carboplatin and paclitaxel display increased tumour apoptosis (39.32%) compared to pembrolizumab treatment (11.39%). Conclusion: PDE viability is preserved following 24h culture with optimal conditions of DMEM-F12 media supplemented with 1% AS. Our results show PDEs are a novel pre-clinical model for predicting drug response in a patient specific setting. Disclosure: Esther Moss - grants: Hope Against Cancer, CRUK development fund.